Voxel-man 3D-navigator inner organs : regional, systemic and radiological anatomy - Hohne, K. H. (Karl Heinz); Universitatskrankenhaus Eppendorf (Hamburg, Germany) Institute of Mathematics and Computer Science in Medicine; Springer Electronic Media; Visible Human Project ([Heidelberg] : Springer Eleectronic Media, 2000)
Based on the Visible Human data set, Voxel-Man 3D-Navigator provides unique reference material not only for medical students, but also for professionals in all medical desciplines involving anatomy and radiology as well as for teachers and interested laymen.
Main CD -- Cross-sections -- stereo scenes
CD is available at Koleksi Media, PHUKM
System requirements : Windows 9x/WindowsNT 4.0/2000 on any PC. For satisfactory performance, the following minimum configuration is required: CPU Pentium 233MHz. recommended 400 MHz or faster; Windows 9x:64 MB RAM (recommended 96 MB or more), WindowsNt/2000;96 MB RAM (recommended 128 or more), 120 MB hard disk space, screen resolution 600x800 pixels (recommended 1024x768 pixels or more), 8x CD-ROM drive (recommended 16x or faster).
Keywords: Thorax -- anatomy & histology; Abdomen -- Anatomy and histology; Pelvis -- anatomy & histology -- atlases